THE CALCULATION METHOD IMPROVEMENT OF THE WHEELSET INERTIA MATRIX WITH REGARDS TO TECHNOLOGICAL ALLOWANCES FOR MANUFACTURING - Kravets, V. V.; Kravets, T. V.; Kharchenko, O. V. (Science and Transport Progress, 2008)
A computation algorithm for inertia matrix of wheel pair taking into account the manufacturing inaccuracies is suggested. It is based on quaternion matrices, which take into consideration the skew of symmetry axes and the shift of substructures within permissible limits.